Anti-urolithiatic Effect of Psiadia Punctulata Leaves Ethanolic Extracts Against Sodium Oxalate-Induced Urolithiasis in Rats - Al-Awar, Mohammed Sadeg A. (Journal of Amran University, 2024)
Kidney stones are rigid mineral and acidic salt deposits that accumulate in concentrated urine, leading to urolithiasis, the third most common urinary tract disorder. Current treatments for urolithiasis have limitations and frequent recurrences. This study aimed to investigate the anti-urolithiatic effects of ethanolic extracts from Psiadia Punctulata leaves on sodium oxalate-induced urolithiasis in rats. Rats were administered orally Psiadia Punctulata leaves ethanolic extract (PPEE) at 200 and 400 mg/kg doses for 14 days to assess its effectiveness against urolithiasis induced by sodium oxalate. Cystone (500 mg/kg) was used as a positive control. The effects of PPEE on body and kidney weights, urinary output and pH levels, urine and serum parameters, renal oxidative and antioxidative markers, and histopathological evaluations were examined. Oral administration of PPEE at 200 and 400 mg/kg doses showed a significant dose-dependent (P<0.01) antiurolithiatic effect, reversing sodium oxalate-induced ion excretion and urinary calcium oxalate concentration. These findings support the traditional use of PPEE for renal calculi management, possibly due to its antioxidant properties identified through phytochemical screening. However, further research is needed to understand the exact mechanism of action